Syphilis Mimicking Other Dermatological Diseases: Reactive Arthritis and Mucha-Habermann Disease - Sueli Coelho da Silva Carneiro; Rodrigo Pirmez; Taciana Rocha de Hollanda; Tullia Cuzzi; Marcia Ramos- (Karger Publishers, 2013)
The authors present two cases of syphilis: one mimicking reactive arthritis and the other Mucha-Habermann disease. Both reports illustrate syphilis as 'the great imitator', a description given by Sir William Osler, and call attention to the strong need for awareness among physicians of all specialties, especially the younger ones, who are not used to seeing this increasingly prevalent disease, as it once was in the past.